Die politische tätigkeit prof. Jurij Bojko- blochyn in deutsch- politischen kreis. Briefwechsel - Blochyn, Dariana (Німецько-Українське Наукове Об’єднання ім. проф. Юрія Бойка-Блохина, Східноєвропейський національний університет імені Лесі Українки, 2019)
The article focuses on German-Ukrainian relations prof. Y. Boykо-Blokhin with politicians, heads of the German government – the Bundestag on the basis of correspondence between the two sides in different directions of the political activity of the professor. In the short article it is not possible to submit a full correspondence with which you can get acquainted with the 3 volumes of Epistolary Yuri Boyko-Blokhin, as well as the political activity in the fourth volume, "The Epistolary Heritage of Y. Boyko-Blochyn: Politics in Ukraine and Germany”, which is preparing for printing.
Keywords: Bundestag; CSU; Franz Josef Strauss; Paneuropa-Union; Otto von Habsburg; Bad Ems; Memorial Table; Alexander II; Cultural Circle of Members from the East; Communist Ideology; LMU; Dr. Knitter; Franz Stauffenberg